2008
DOI: 10.1111/j.1532-5415.2008.01926.x
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Preventive Effect of Oral Hygiene on Pneumonia and Respiratory Tract Infection in Elderly People in Hospitals and Nursing Homes: Effect Estimates and Methodological Quality of Randomized Controlled Trials

Abstract: The objective of this study was to investigate the preventive effect of oral hygiene on pneumonia and respiratory tract infection, focusing on elderly people in hospitals and nursing homes, by systematically reviewing effect estimates and methodological quality of randomized controlled trials (RCTs) and to provide an overview of additional clinical studies in this area. Literature searches were conducted in the Medline database, the Cochrane library databases, and by hand-searching reference lists. Included pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
230
0
17

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(255 citation statements)
references
References 32 publications
5
230
0
17
Order By: Relevance
“…Individuals with DM1 who have poor OH should be identified and receive extra prophylactic dental care. DM1 is a progressive disease with a high risk of developing cardiac disease, respiratory dysfunction, and dysphagia and the importance of a healthy mouth is therefore of extra importance (Sjögren et al 2008). In addition, there are certain risks related to general anesthesia (Rogers & Clyburn 2004), which makes preventive oral care highly justified in patients who will require some kind of sedation in connection with dental treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with DM1 who have poor OH should be identified and receive extra prophylactic dental care. DM1 is a progressive disease with a high risk of developing cardiac disease, respiratory dysfunction, and dysphagia and the importance of a healthy mouth is therefore of extra importance (Sjögren et al 2008). In addition, there are certain risks related to general anesthesia (Rogers & Clyburn 2004), which makes preventive oral care highly justified in patients who will require some kind of sedation in connection with dental treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Van der Mareel-Wiernik et al recommended tooth brushing after each meal, cleaning removable prostheses once a day, and professional oral health care once a week as the best regimen to reduce the incidence of aspiration pneumonia (van der MaarelWierink et al 2013). A systematic review concluded from 4 RCTs that 1 in 10 deaths from pneumonia in elderly nursing home residents may be prevented by improving oral hygiene (Sjogren et al 2008). …”
Section: Effectiveness Of Oral Care In Reducing the Risk Of Pneumoniamentioning
confidence: 99%
“…Para além disso, constituem, muitas vezes, a evidência primária de doenças sistémicas, nomeadamente em casos de diabetes ou HIV/SIDA (Griffin et al,2012;Petersen, Bourgeois, Bratthall, Ogawa, Estupinan-Day, & Ndiaye, 2005). Para além de que, melhores cuidados de higiene oral parecem prevenir infeções respiratórias e morte por pneumonia em idosos nos hospitais e lares (Sjögren, Nilsson, Forsell, Johansson, & Hoogstraate, 2008) e ainda a escovagem frequente de dentes pode estar associada a níveis baixos de doença cardiovascular (Oliveira, Watt, & Hamer, 2010).…”
unclassified